2021
DOI: 10.3390/vaccines9080888
|View full text |Cite
|
Sign up to set email alerts
|

Dental Students’ Knowledge and Attitudes about Human Papillomavirus Prevention

Abstract: The purpose of the current study was to assess knowledge and attitudes about human papillomavirus (HPV) and HPV vaccination for oropharyngeal cancer (OPC) prevention in first-year through fourth-year dental students. Methods: In this cross-sectional quantitative study, surveys assessed knowledge and attitudes about HPV, HPV-related OPC, and HPV vaccination of incoming first-year dental students (D1), outgoing first- and second-year dental students (D1–D2), and outgoing third- and fourth-year dental students (D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 16 publications
2
2
0
Order By: Relevance
“…As the care for patients with HPV-related illnesses and cancer required input from providers in different fields of medicine and dentistry, it is imperative that all providers are familiar with the most up-to-date HPV cancer prevention practices. Similar to our study, Wright et al identified an important knowledge gap in baseline HPV understanding among dental students across all 4 years at an accredited US dental school [12]. Laitman et al also reported an educational gap in HPV knowledge among medical students and found that only 50% of medical students surveyed from 10 medical schools in New York State knew about the association of HPV and head and neck cancers [13].…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…As the care for patients with HPV-related illnesses and cancer required input from providers in different fields of medicine and dentistry, it is imperative that all providers are familiar with the most up-to-date HPV cancer prevention practices. Similar to our study, Wright et al identified an important knowledge gap in baseline HPV understanding among dental students across all 4 years at an accredited US dental school [12]. Laitman et al also reported an educational gap in HPV knowledge among medical students and found that only 50% of medical students surveyed from 10 medical schools in New York State knew about the association of HPV and head and neck cancers [13].…”
Section: Discussionsupporting
confidence: 87%
“…Similar to our study, Wright et al identified an important knowledge gap in baseline HPV understanding among dental students across all 4 years at an accredited US dental school [ 12 ]. Laitman et al also reported an educational gap in HPV knowledge among medical students and found that only 50% of medical students surveyed from 10 medical schools in New York State knew about the association of HPV and head and neck cancers [ 13 ].…”
Section: Discussionsupporting
confidence: 85%
“…HAPO-02-K-012-2022-11-1257) and King Abdulaziz University in Jeddah, SA (approval no. 123- [10][11][12][13][14][15][16][17][18][19][20][21][22].…”
Section: Ethical Consideration and Informed Consentmentioning
confidence: 99%
“…Globally, the dental bachelor programs offer hands-on experience, with students actively engaging with patients in clinics. Thus, dental students' knowledge of HPV-OPSCC is critical in identifying risk factors, prompting vaccination, and facilitating early intervention, thereby significantly contributing to public health initiatives aimed at reducing the burden of HPV-associated diseases [20]. In SA, previous studies identified a lack of HPV knowledge among dental students, necessitating curriculum enhancements, yet research on their understanding of HPV-OPSCC, attitudes toward HPV vaccination, and their roles in disease prevention and patient education remains limited [21,22].…”
Section: Introductionmentioning
confidence: 99%